Expression, Purification and Crystallization of the Herpesvirus Nuclear Egress Complex (NEC) - Bigalke, Janna M. (Bio Protoc, 2016)
The protocol describes the production and crystallization of the soluble form of the nuclear egress complex (NEC) from Herpes simplex virus 1 and Pseudorabies virus. The NEC is a heterodimer that consists of conserved proteins UL31 and UL34. NEC oligomerization deforms the inner nuclear membrane around the capsid in infected cells, thereby mediating capsid budding into the perinuclear space during nuclear egress. We have successfully developed a protocol for large-scale preparation of highly pure NEC from two different viruses in a prokaryotic expression system, which enabled us to crystallize these viral protein complexes and determine their structures. This procedure may be adapted to purify and crystallize other soluble protein complexes.